Fast and effective soft links. (11th April 2012) - Akinyemi, John A.; Clarke, Charles L. A.
SUMMARY Inspired by requirements traceability problems, we present a method for implementing fast and effective hypertext links to specific locations within documents. These soft links do not depend on tags, markup, or closed tool sets, yet they can generally survive extensive edits to a document collection, allowing the targets of these links to be located in real collections after years of ongoing and frequent changes. We base our implementation of soft links on an existing passage retrieval algorithm, originally designed for question answering. The method treats the text surrounding the target of a soft link as a passage to be retrieved, creates a signature for that passage, and resolves the link by searching for the passage. The method is evaluated over a large collection of text and two large collections of source code, one written in the C programming language and one written in Java. Copyright © 2012 John Wiley & Sons, Ltd.